A música sob o interdito: a ambiguidade da relação entre a Igreja e a polifonia musical no século XIV - Esperandio, Thiago José (2010)
It intends to analyze the social history of the music, which, around XI e XII centuries, is aesthetically innovated at the same time that several social changes happen. This new music (polyphonic) is a technical variation of the Gregorian Chant (monophonic). Its evolution happens mainly in the church environment, but its relation with the clerics was not always peaceful. Because it was developed in the urban cathedrals-churches and universities, it did not totally join with the church tradition, it used to represent a deviation from the church, which, until that moment, had as its scholars centers, the monastery. This fact was enough to generate doubts about using or not this music in the churches celebrations. Although these doubts existed, they had never taken the clerics to any arbitrary actions in relation to the polyphonic music. During the XII and XIII centuries, a social stability and the church hegemony contributed for the dialog between clerics and musicians, but the actions of the temporal power against the church in the XIV century, made it look more carefully to the elements that the secular society brought to its practices in the celebrations. This is when Pope John XXII decrees the bull Docta Sanctorum Patrum prohibiting the practice of polyphonic music, mainly the one that were practiced by new schools and had secular characteristics, in churches celebration . Studying the reasons that influenced the Pope to take this action is the principal objective of this study